2011
DOI: 10.1007/s00122-011-1544-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of a gibberellin 20-oxidase gene is associated with multiple agronomic and quality traits in barley

Abstract: The use of dwarfing genes has resulted in the most significant improvements in yield and adaptation in cereal crops. The allelic dwarfing gene sdw1/denso has been used throughout the world to develop commercial barley varieties. The sdw1 gene has never been used successfully for malting barley, but only for a large number of feed varieties. One of the gibberellin 20-oxidase genes (Hv20ox₂) was identified as the candidate gene for sdw1/denso. Semi-quantitative real-time RT-PCR revealed that Hv20ox₂ was expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 48 publications
6
69
0
Order By: Relevance
“…For example, mutations of semi-dwarf1 (sd1) in rice1923 and Reduced height (Rht) in wheat20, which encode a GA biosynthesis enzyme and a dominant suppressor protein of GA signal transduction, respectively, have been widely used to improve lodging resistance in these crops, resulting in the success of the “green revolution”. It has also been reported that the semi-dwarfism of barley, sdw1/denso , widely introgressed into cultivars grown in Europe, probably results from a defect in an ortholog of rice SD1 242526. That GA-related mutations have been used for improving lodging resistance in rice, wheat, and barley, demonstrates the importance of decreasing the GA level, or sensitivity to GA, in reducing plant heights.…”
Section: Discussionmentioning
confidence: 98%
“…For example, mutations of semi-dwarf1 (sd1) in rice1923 and Reduced height (Rht) in wheat20, which encode a GA biosynthesis enzyme and a dominant suppressor protein of GA signal transduction, respectively, have been widely used to improve lodging resistance in these crops, resulting in the success of the “green revolution”. It has also been reported that the semi-dwarfism of barley, sdw1/denso , widely introgressed into cultivars grown in Europe, probably results from a defect in an ortholog of rice SD1 242526. That GA-related mutations have been used for improving lodging resistance in rice, wheat, and barley, demonstrates the importance of decreasing the GA level, or sensitivity to GA, in reducing plant heights.…”
Section: Discussionmentioning
confidence: 98%
“…This lack of effect on seed production is probably due to expression of GA20ox paralogs, mainly GA20ox2 (8). Similarly, GA20ox2 mutations in rice and barley do not display tradeoffs (5,6,27). By contrast, mutations in early steps of GA biosynthesis have been associated with negative pleiotropic effects, such as the absence of seed germination shown by ga1 null mutants or the reduced fertility and altered flower development observed even in leaky GA1 alleles (13).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sdw1/denso is expressed all of the tissues and affects many developmental processes through GA level [7, 8]. ari-e also reduces plant height and is related with lots of agronomic traits, such as erect juvenile growth habit, earliness, compact inflorescene, short awns, small seed size and cell size reduction in leaf blades [19, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that ari-e may be involved in different developmental processes. Furthermore, reduced expression of HvGA20ox 2 was identified in various organs in denso semi-dwarf mutant compared with tall variety [7]. Rieu et al [69] reported that AtGA20ox 1 (also named as semi-dwarf gene ga5 ) was showed different expression in different tissues, and at different developmental stages.…”
Section: Discussionmentioning
confidence: 99%